-23=6-5n-4

Simple and best practice solution for -23=6-5n-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23=6-5n-4 equation:


Simplifying
-23 = 6 + -5n + -4

Reorder the terms:
-23 = 6 + -4 + -5n

Combine like terms: 6 + -4 = 2
-23 = 2 + -5n

Solving
-23 = 2 + -5n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '5n' to each side of the equation.
-23 + 5n = 2 + -5n + 5n

Combine like terms: -5n + 5n = 0
-23 + 5n = 2 + 0
-23 + 5n = 2

Add '23' to each side of the equation.
-23 + 23 + 5n = 2 + 23

Combine like terms: -23 + 23 = 0
0 + 5n = 2 + 23
5n = 2 + 23

Combine like terms: 2 + 23 = 25
5n = 25

Divide each side by '5'.
n = 5

Simplifying
n = 5

See similar equations:

| 415441*10= | | 4(x-7)-2=2(x-3) | | 5k-2k=-21 | | 368317*10= | | 10x-8=9x-5 | | 458000*8= | | -16=-3p+p | | 449000*8= | | 3n=4n-4 | | 8n+3n=-22 | | 2x+26=44 | | 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) |

Equations solver categories